Academic publishing requires linguistically inclusive policies - Arenas-Castro, Henry; Berdejo-Espinola, Violeta; Chowdhury, Shawan; Rodríguez-Contreras, Argelia; James, Aubrie R.M.; Raja, Nussaïbah Begum; Dunne, Emma; Bertolino, Sandro; Emidio, Nayara Braga; Derez, Chantelle M.; Drobniak, Szymon M.; Fulton, Graham R.; et al. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2024)
Scientific knowledge is produced in multiple languages but is predominantly published in English. This practice creates a language barrier to generate and transfer scientific knowledge between communities with diverse linguistic backgrounds, hindering the ability of scholars and communities to address global challenges and achieve diversity and equity in science, technology, engineering and mathematics (STEM). To overcome those barriers, publishers and journals should provide a fair system that supports non-native English speakers and disseminates knowledge across the globe. We surveyed policies of 736 journals in biological sciences to assess their linguistic inclusivity, identify predictors of inclusivity, and propose actions to overcome language barriers in academic publishing. Our assessment revealed a grim landscape where most journals were making minimal efforts to overcome language barriers. The impact factor of journals was negatively associated with adopting a number of inclusive policies whereas ownership by a scientific society tended to have a positive association. Contrary to our expectations, the proportion of both open access articles and editors based in non-English speaking countries did not have a major positive association with the adoption of linguistically inclusive policies. We proposed a set of actions to overcome language barriers in academic publishing, including the renegotiation of power dynamics between publishers and editorial boards.
CRIS-Team Scopus Importer:2024-03-22
Keywords: academic publishing; biological sciences; inclusivity; language barriers; society journals

Addressing priority questions of conservation science with palaeontological data - Kießling, Wolfgang; Raja, Nussaïbah Begum; Roden, Vanessa; Turvey, Samuel T.; Saupe, Erin E. (Philosophical Transactions of the Royal Society B-Biological Sciences, 2019)

Ancient Reef Traits, a database of trait information for reef-building organisms over the Phanerozoic - Raja Schoob, Nussaibah Begum; Dimitrijevic, Danijela; Krause, Mihaela Cristina; Kießling, Wolfgang (Scientific Data, 2022)
Trait-based approaches are increasingly relevant to understand ecological and evolutionary patterns. A comprehensive trait database for extant reef corals is already available and widely used to reveal vulnerabilities to environmental disturbances including climate change. However, the lack of similar trait compilations for extinct reef builders prevents the derivation of generalities from the fossil record and to address similar questions. Here we present the Ancient Reef Traits Database (ARTD), which aims to compile trait information of various reef-building organisms in one single repository. ARTD contains specimen-level data from both published and unpublished resources. In this first version, we release 15 traits for 505 genera and 1129 species, comprising a dataset of 17,841 trait values of Triassic to mid-Holocene scleractinian corals, the dominant reef-builders in the modern ocean. Other trait data, including for other reef-building organisms, are currently being collated.
CRIS-Team WoS Importer:2022-07-29

A reconstruction of Turkey's potential natural vegetation using climate indicators - Raja, Nussaïbah Begum; Aydin, Olgu; Cicek, Ihsan; Turkoglu, Necla (Journal of Forestry Research, 2019)
Turkey, containing three of the world's biodiversity hotspots, is a hub for genetic biodiversity. However, the vegetation cover has drastically changed in recent decades as a result of substantial transformations in land-use practices. A map of the potential natural vegetation can be used to represent the biodiversity of a country, and therefore a reference to effectively develop conservation strategies. The multinomial logistic regression is used to simulate the probability of different biomes occurring in the country using elevation, climatological data and natural vegetation data. A correlation test was applied to the climatological data to determine which predictors influence vegetation the most. These were temperature, precipitation, relative humidity and cloudiness. The Ordinary Kriging method was employed to transform the data into the format for the multinomial logistic regression model. The model showed that temperature was the most influencing factor with respect to Turkey's vegetation and distribution follows a similar distribution as the various macroclimates. Broadleaf forests are mostly found in the Black Sea region, which is also the wettest region of the country. The Marmara region is the only other region where there are broadleaf forests. Mixed forests and shrublands are mostly located in Central Anatolia due to the region's low humidity which favours herbaceous flora. Coniferous forests were dominant in the Aegean and Mediterranean regions, attributed to high temperatures.
CRIS-Team WoS Importer:2019-11-15

Author Correction: Colonial history and global economics distort our understanding of deep-time biodiversity (Nature Ecology & Evolution, (2021), 10.1038/s41559-021-01608-8) - Raja, Nussaïbah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2022)
In the version of this article initially published, the designation “Central” America was omitted in an Extended Data Fig. 2c panel heading and the caption as well as in the Extended Data Fig. 3 caption. The figure and captions have been updated to clarify “Central and South America” in each instance.
CRIS-Team Scopus Importer:2022-02-11

Bulanık Mantık Yöntemiyle Sera Gölü Çevresinin Heyelan Duyarlılık Analizi - Aydın, Olgu; Raja, Nussaïbah Begum (Afet ve Risk Dergisi, 2024)
Landslides are a frequent occurrence in the Black Sea Region, mainly due to factors such as geomorphological and lithological conditions, soil properties and humidity, land use, along with effective precipitation. Landslide susceptibility assessments are vital to ensure that necessary precautions are taken to mitigate against landslides so as to help reduce possible loss of life and property. In addition, landslide susceptibility assessments are also important for future land development plans. The aim of the study is to carry out a landslide susceptibility assessment using the artificial intelligence-based Fuzzy Logic method of Sera Lake around Trabzon, Akçaabat district. The variables used in our model are: slope, aspect, slope shape, relative relief, lithology, distance to the river and topographic humidity index. The landslide susceptibility analysis of the Sera Lake environment provided an R2 value of 0.67 and RMSE and MAE values close to “0”. This suggests that our method was quite good at evaluating landslide susceptibility in our study area. Landslide sensitive areas correspond to an important part of the study area. The results of the study are important in terms of taking necessary measures against economic, social, cultural and environmental damages of landslides and making future plans in order to show the areas that may be sensitive to landslides.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Fuzzy Logic; Landslide; Landslide Susceptibility Map; Surrounding of Sera Lake

Census-based estimates of Mediterranean Oligocene–Miocene reef carbonate production - Kießling, Wolfgang; Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Frühbeißer, Kerstin; Vescogni, Alessandro; Bosellini, Francesca R. (Facies, 2024)
Census-based approaches to reefal carbonate budgets are increasingly being used to project the near-future fate of tropical coral reefs. Some of the census parameters are difficult to achieve in fossil reef systems, which may be the reason why no census-based estimates of fossil reef carbonate production have been published until now. Here, we apply a census-based estimate of gross carbonate production in two reef systems from southeastern Italy to (1) test if reasonable estimates are possible and (2) assess the variability of carbonate production rates over time and reef environment. We confirm that estimates of late Oligocene and late Miocene reef gross carbonate production are within the range of modern coral reefs with the late Oligocene reef front showing the greatest carbonate production (6.1 ± 1.3 kg CaCO3 m−2 year−1) and the late Miocene reef front exhibiting the lowest production (1.7 ± 0.5 kg CaCO3 m−2 year−1). The decline of reef carbonate production from the Oligocene to the Miocene is accompanied by a decline of reef builder biodiversity but driven by the lower coral cover and coral growth rates in the Miocene. The decline of reefal carbonate production may be related to late Cenozoic cooling.
Keywords: Reefs; Carbonate budget; Corals; Growth rates; Oligocene; Miocene; Climate change

Changes in corallite sizes of scleractinian corals across major hyperthermal events - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (Progressive Palaeontology 2021 - Online, 2021)
Global warming today is taking its toll on coral reefs globally, particularly affecting scleractinian corals which rely on their symbionts for nutrition. In the past, hyperthermal events have probably triggered evolutionary losses and gains of symbiosis in corals. Accordingly, we expect photosymbiotic corals to be more strongly affected than non-symbiotic corals. Corallite sizes have been used as a proxy for the efficacy of photosymbiosis with smaller corallite sizes associated with higher photosymbiotic autotrophy in colonial corals. Using a new database on corallite sizes of fossil corals collected from existing literature and data on modern corals from the Coral Trait Database combined with occurrences from the Paleobiology Database, we test how the dependency on photosynthetic diet in corals may have increased their extinction risk. We expect corals to be selected against small corallite sizes during hyperthermal events. Based on a survey of 353 fossil and recent coral genera we establish trends in corallite sizes across the Triassic–Jurassic, Pliensbachian–Toarcian, Barremian–Aptian, Cenomanian–Turonian, and Paleocene–Eocene. We find a significant increase in corallite diameter of all corals at three of these events. Colonial corals had 0.8 times larger corallites in the Aptian than in the Barremian suggesting stronger heterotrophy at this hyperthermal event. However, generalized linear modelling suggests that the extinction of scleractinian corals seems to be non-selective with regards to their corallite sizes. This indicates that processes other than warming, such as increased sediment input could be the cause of this change.<br

Chronosphere: Earth System History Variables - Kocsis, Ádám; Raja, Nussaïbah Begum (GSA 2020 Connects Online, 2020)
Researchers focusing on global-scale ecological and evolutionary patterns are faced with the overwhelmingly increasing volume and diversity of data compilations. The complexity of the relevant research questions necessitates the interconnected use of multiple datasets (the source variables) that are often regularly updated. Finding these data and incorporating them in the analytical workflow can be time consuming and often lead to difficulties and conflicts in version control. The goal of the ‘chronosphere’ project is to offer a portal to these data and to allow their immediate use by compiling frequently accessed representations on a server that keeps track of different versions. These data are available through an R package of the same name (available on the CRAN servers), that downloads a specific version of a dataset and attaches it to the R environment. The project focuses on data used in biogeography, macroecology and macroevolution, from large datasets to small tables published as supplementary information to research articles. Currently available data include major sources such as the Paleobiology Database, the PaleoReefs Database, and the paleogeographic reconstructions of the PaleoMAP project. ‘chronosphere’ will also be used to distribute the output of BRIDGE HadCM3L family deep-time climate models. To facilitate the use of deep-time spatial data, the R package includes functions that utilize either the GPlates Web Service or the GPlates desktop application to reconstruct the positions of present-day coordinates and spatial features using a user-specified reconstruction model. An efficient container class is also implemented to facilitate the work with raster and vector data layers that are organized in multi-dimensional arrays. These features were proven especially useful in the classroom environment, where the fast download and transformation of data are important. Providing data in a consistent form within the R programming framework, ‘chronosphere’ allows the fast reproducibility, and ultimately the tracing of scientific results with the same codebas

Colonial history and global economics distort our understanding of deep-time biodiversity - Raja Schoob, Nussaibah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2021)
Sampling biases in the fossil record distort estimates of past biodiversity. However, these biases not only reflect the geological and spatial aspects of the fossil record, but also the historical and current collation of fossil data. We demonstrate how the legacy of colonialism and socioeconomic factors, such as wealth, education and political stability, impact the global distribution of fossil data over the past 30 years. We find that a global power imbalance persists in palaeontology, with researchers in high- or upper-middle-income countries holding a monopoly over palaeontological knowledge production by contributing to 97% of fossil data. As a result, some countries or regions tend to be better sampled than others, ultimately leading to heterogeneous spatial sampling across the globe. This illustrates how efforts to mitigate sampling biases to obtain a truly representative view of past biodiversity are not disconnected from the aim of diversifying and decolonizing our discipline.

Colonialism shaped today’s biodiversity - Raja, Nussaïbah Begum (Nature Ecology & Evolution, 2022)
CRIS-Team Scopus Importer:2022-10-28

Coral community shifts across major reef crises - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (ICRS 2021, 14th International Coral Reef Symposium, 2021)
Coral communities today are negatively affected by anthropogenic greenhouse gas release causing global warming and ocean acidification. Natural greenhouse gas release by massive volcanism is thought to have caused one of the Big Five mass extinctions at the end of the Triassic period (200 million years ago). This hyperthermal event triggered one of the greatest reef crises and the most substantial evolutionary crisis in the history of scleractinian corals. While the diversity dynamics of corals are well studied, research on changes in community composition at this time is still lacking. We provide a quantitative assessment of community changes at the level of morphological traits (ie corallite sizes, growth form, and colony form). Using our new Reef Traits Database (RTD), we show that corallite sizes of colonial corals increased substantially after the end-Triassic reef crisis. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities. We conclude that a change towards increasing heterotrophy in reef coral communities best explains the observations across the end-Triassic reef crisis. Additionally, we test how much of the trend in corallite size is governed by selective extinction, origination, and changes in relative abundance across coral communities. Therefore, the fossil record showcases the balance of evolutionary adaptation versus extinction and the lasting community changes in response to climate change over longer time frames than we could cover by studying the extant coral communities.<br

Corallite sizes and their link to extinction risk of scleractinian corals across the Triassic-Jurassic boundary - Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Kießling, Wolfgang (GSA 2020 Connects Online, 2020)
The end-Triassic mass extinction and reef crisis was a significant crisis in the evolution of scleractinian corals. The crisis is thought to have been caused by volcanically induced global warming. Accordingly, we would expect photosymbiotic corals to be more strongly affected than non-symbiotic corals. However, although corallite integration has decreased across the Triassic-Jurassic boundary, the extinction of scleractinian corals seems to be non-selective with regards to their inferred photosymbiotic mode. Using our new Reef Traits Database (RTD) we test how corallite sizes may have changed across the Triassic-Jurassic boundary. Corallite sizes have been used as a proxy for the efficacy of photosymbiosis with smaller corallite sizes associated with higher photosymbiotic autotrophy in colonial corals. As such, we use maximum corallite diameter to investigate how the dependency on a photosynthetic diet may have increased the extinction risk of certain corals at the end-Triassic mass extinction. Based on a survey of nearly 2000 measurements we establish trends in corallite sizes across the Triassic-Jurassic. We find that there was a significant increase of corallite diameter at the Triassic-Jurassic boundary suggesting stronger heterotrophy. Corallite sizes were 1.8 times larger after the mass extinction, which is the strongest change across the entire 100 myr interval. Generalized linear modeling suggests that the increase of corallite diameters was due to the selective extinction of corals with smaller corallite

Corallite sizes of reef corals: decoupling of evolutionary and ecological trends - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (Paleobiology, 2023)
Corallite sizes reflect a continuum in the efficacy of photosymbiosis in colonial reef corals, with smaller corallite sizes generally associated with higher autotrophy. Using a large compilation of reef-coral traits and corallite diameters as a proxy, we test here the hypothesis that photosymbiotic efficacy has increased over the evolutionary history of scleractinian corals. To gain a more comprehensive understanding of the evolutionary versus ecological patterns of corallite sizes of reef corals, we used three analytical methods: (1) occurrences-weighted within-bin analyses as a proxy for abundance or ecological dominance to depict ecological patterns; (2) unweighted range-through analyses; and (3) unweighted sampled-in-bin analyses to represent diversity in terms of taxonomic richness, enabling us to trace evolutionary patterns. By-genus, range-through analysis indicates a slightly positive trend of corallite sizes toward the Recent. However, the occurrences-weighted assessment shows a pronounced negative trend of corallite sizes in colonial corals since the Mesozoic. Random walk and directional evolution are both statistically supported to explain this long-term decrease. A driven trend is evolutionarily plausible, giving reef corals a selective advantage in the oligotrophic environments they largely occupy today.

Data equity in paleobiology: progress, challenges, and future outlook - Dunne, Emma; Chattopadhyay, Devapriya; Dean, Christopher D.; Dillon, Erin M.; Dowding, Elizabeth; Godoy, Pedro L.; Smith, Jansen A.; Raja, Nussaïbah Begum (Paleobiology, 2025)
In the last 50 years, the field of paleobiology has undergone a computational revolution that opened multiple new avenues for recording, storing, and analyzing vital data on the history of life on Earth. With these advances, the amount of data available for research has grown, but so too has our responsibility to ensure that our data tools and infrastructures continue to innovate in order to best serve our diverse community. This review focuses on data equity in paleobiology, an aspirational goal, wherein data in all forms are collected, stored, shared and analyzed in a responsible, equitable, and sustainable manner. While there have been many advancements across the last five decades, inequities persist. Our most significant challenges relate to several interconnected factors, including ethical data collection, sustainable infrastructure, socioeconomic biases, and global inequalities. We highlight the ways in which data equity is critical for paleobiology and stress the need for collaborative efforts across the paleobiological community to urgently address these data equity challenges. We also provide recommendations for actions from individuals, teams, academic publishers, and academic societies in order to continue enhancing data equity and ensuring an equitable and sustainable future for our field.
CRIS-Team Scopus Importer:2025-05-09

Digging deeper into colonial palaeontological practices in modern day Mexico and Brazil - Cisneros, Juan; Raja Schoob, Nussaibah Begum; Ghilardi, Aline Marcele; Dunne, Emma; Pinheiro, Felipe; Regalado Fernández, Omar Rafael; Sales, Marcos; Rodríguez-de la Rosa, Rubén; Miranda-Martínez, Adriana; González-Mora, Sergio; Bantim, Renan; de Lima, Flaviana; et al. (Royal Society Open Science, 2022)
Scientific practices stemming from colonialism, whereby middle- and low-income countries supply data for high-income countries and the contributions of local expertise are devalued, are still prevalent today in the field of palaeontology. In response to these unjust practices, countries such as Mexico and Brazil adopted protective laws and regulations during the twentieth century to preserve their palaeontological heritage. However, scientific colonialism is still reflected in many publications describing fossil specimens recovered from these countries. Here, we present examples of ‘palaeontological colonialism’ from publications on Jurassic–Cretaceous fossils from NE Mexico and NE Brazil spanning the last three decades. Common issues that we identified in these publications are the absence of both fieldwork and export permit declarations and the lack of local experts among authorships. In Mexico, access to many fossil specimens is restricted on account of these specimens being housed in private collections, whereas a high number of studies on Brazilian fossils are based on specimens illegally reposited in foreign collections, particularly in Germany and Japan. Finally, we outline and discuss the wider academic and social impacts of these research practices, and propose exhaustive recommendations to scientists, journals, museums, research institutions and government and funding agencies in order to overcome these practices.<br

Ethics, law, and politics in palaeontological research: The case of Myanmar amber - Dunne, Emma; Raja, Nussaïbah Begum; Stewens, Paul P.; Zin-Maung-Maung-Thein; Zaw, Khin (Communications Biology, 2022)
Fossil material in amber from Myanmar can provide important insights into mid-Cretaceous forest ecosystems. However, Myanmar amber has been receiving increased international attention due to reported links between amber mining and the ongoing humanitarian crisis in northern Myanmar, as well as the legal issues associated with its exportation. Here, we conduct a bibliometric analysis of Myanmar amber publications (1990–2021) and demonstrate how research interest in Myanmar amber is explicitly linked to major political, legal, and economic changes. An analysis of the authorship networks for publications on amber inclusions reveals how current research practices have excluded Myanmar researchers from the field. In addition, the international trade of Myanmar amber with fossil inclusions falls into a legal ‘grey-zone’ which continues to be exploited. This case study vividly demonstrates that systemic changes, alongside an increased awareness of inequitable research practices amongst the broader scientific and allied communities, are urgently needed to curb illegal practices in palaeontology.
CRIS-Team Scopus Importer:2022-10-14

fossilbrush: An R package for automated detection and resolution of anomalies in palaeontological occurrence data - Flannery-Sutherland, Joseph T.; Raja, Nussaïbah Begum; Kocsis, Ádám; Kießling, Wolfgang (Methods in Ecology and Evolution, 2022)
Fossil occurrence databases are indispensable resources to the palaeontological community, yet present unique data cleaning challenges. Many studies devote significant attention to cleaning fossil occurrence data prior to analysis, but such efforts are typically bespoke and difficult to reproduce. There are also no standardised methods to detect and resolve errors despite the development of an ecosystem of cleaning tools fuelled by the concurrent growth of neontological occurrence databases. As fossil occurrence databases continue to increase in size, the demand for standardised, automated and reproducible methods to improve data quality will only grow. Here, we present semi-automated cleaning solutions to address these issues with a new R package fossilbrush. We apply our cleaning protocols to the Paleobiology Database to assess the prevalence of anomalous entries and the efficacy and impact of our methods. We find that anomalies may be effectively resolved by comparison against a published compendium of stratigraphic ranges, improving the stratigraphic quality of the data, and through methods which detect outliers in taxon-wise occurrence stratigraphic distributions. Despite this, anomalous entries remain prevalent throughout major clades, with often more than 30% of genera in major fossil groups (e.g. bivalves, echinoderms) displaying stratigraphically suspect occurrence records. Our methods provide a way to flag and resolve anomalous taxonomic data before downstream palaeobiological analysis and may also aid in the automation and targeting of future cleaning efforts. We stress, however, that our methods are semi-automated and are primarily for the detection of potential anomalies for further scrutiny, as full automation should not be a substitute for expert vetting. We note that some of our methods do not rely on external databases for anomaly resolution and so are also applicable to occurrences in neontological databases, expanding the utility of the fossilbrush R package.
CRIS-Team WoS Importer:2022-09-02

Fossil Trafficking, Fraud, and Fakery - Raja Schoob, Nussaibah Begum; Dunne, Emma (Art Crime in Context, 2022)
The fascination with ancient flora and fauna is a centuries-old phenomenon and is one of the main drivers of fossil crimes. Fossils have been sought by the rich and famous since the advent of colonialism, propelling development in the field of palaeontology but also in how fossils make their way through various, sometimes illegal, corridors to end up in museums and collections across the world. As demand for fossils increased in the nineteenth century, so did commercial avenues for these objects that were being sold not only to private individuals but also to scientific institutions. The most complete and visually impressive fossils in terms of size or uniqueness determine the market value of these fossils with some selling for millions of United States dollars. This has also led to the tampering or forging of fossils by many dealers in an attempt to inflate prices. While fossil crimes have been prevalent for centuries, the legal frameworks within which these crimes can be controlled or stopped are regularly challenged or even circumvented not only due to the lack of enforcements of these regulations but also due to how paleontological objects are classified in the first place as well as other legal loopholes.<br

Global warming generates predictable extinctions of warm- and cold-water marine benthic invertebrates via thermal habitat loss - Reddin, Carl J.; Aberhan, Martin; Raja, Nussaïbah Begum; Kocsis, Ádám (Global Change Biology, 2022)
Anthropogenic global warming is redistributing marine life and may threaten tropical benthic invertebrates with several potential extinction mechanisms. The net impact of climate change on geographical extinction risk nevertheless remains uncertain. Evidence of widespread climate-driven extinctions and of potentially unidentified mechanisms exists in the fossil record. We quantify organism extinction risk across thermal habitats, estimated by paleoclimate reconstructions, over the past 300 million years. Extinction patterns at seven known events of rapid global warming (hyperthermals) differ significantly from typical patterns, resembling those driven by global geometry under simulated global warming. As isotherms move poleward with warming, the interaction between the geometry of the globe and the temperature-latitude relationship causes an uneven loss of thermal habitat and a bimodal latitudinal distribution of extinctions. Genera with thermal optima warmer than similar to 21 degrees C show raised extinction odds, while extinction odds continually increase for genera with optima below similar to 11 degrees C. Genera preferring intermediate temperatures generally have no additional extinction risk during hyperthermals, except under extreme conditions as the end-Permian mass extinction. Widespread present-day climate-driven range shifts indicate that occupancy loss is already underway. Given the most-likely projections of modern warming, our model, validated by seven past hyperthermal events, indicates that sustained warming has the potential to annihilate cold-water habitat and its endemic species completely within centuries.
CRIS-Team WoS Importer:2022-07-29

How does Citizen Science matter for policy? Analyzing the impact of citizen science in policy making - Almomani, Abeer; Awai, Erdoo Paula; Bonn, Aletta; de Barros, Ingrid Almeida; Friedly, Colleen; Gharesifard, Mohammad; Hecker, Susanne; Kartika, Erlinda Cahya; Kraft, Anne; Matthus, Elsa; Peter, Maria; Raja Schoob, Nussaibah Begum; et al. (iDiv Annual Conference 2019, 2019)
Citizen Science has been proven to support policy making (Bio Innovation Service, 2018),yet harnessing the full potential of Citizen Science requires further understanding of the particular areas of the policy development process where different Citizen Science projects have contributed. Using the policy cycle framework (Howlett&Ramesh, 2003) we assessed 500 Citizen Science projects reported in EU inventory and conducted in-depth analysis of 25 case studies. Our study aims to determine the impact of citizen science projects on the policy cycle.<br

ImageJ and 3D Slicer : open source 2 / 3D morphometric software - Pye, Fiona; Raja Schoob, Nussaibah Begum; Shirley, Bryan; Kocsis, Ádám; Hohmann, Niklas; Murdock, Ducan JE; Jarochowska, Emilia (Open Data and Analysis: from morphology to evolutionary patterns, 2019)
In a world where an increasing number of resources are hidden behind paywalls and monthly subscriptions, it is becoming crucial for the scientific community to invest energy into freely available, community-maintained systems. Open-source software projects offer a solution, with freely available code which users can utilise and modify, under an open source licence. In addition to software accessibility and methodological repeatability, this also enables and encourages the development of new tools. As palaeontology moves towards data driven methodologies, it is becoming more important to acquire and provide high quality data through reproducible systematic procedures. Within the field of morphometrics, it is vital to adopt digital methods that help mitigate human bias from data collection. In addition,m mathematically founded approaches can reduce subjective decisions which plague classical data. This can be further developed through automation, which increases the efficiency of data collection and analysis. With these concepts in mind, we introduce two open-source shape analysis software, that arose from projects within the medical imaging field. These are ImageJ, an image processing program with batch processing features, and 3DSlicer which focuses on 3D informatics and visualisation. They are easily extensible using common programming languages, with 3DSlicer containing an internal python interactor, and ImageJ allowing the incorporation of several programming languages within its interface alongside its own simplified macro language. Additional features created by other users are readily available, on GitHub or through the software itself. In the examples presented, an ImageJ plugin “FossilJ” has been developed which provides semi-automated morphometric bivalve data collection. 3DSlicer is used with the extension SPHARM-PDM, applied to synchrotron scans of coniform conodonts for comparative morphometrics, for which small assistant tools have been created.

Improving the relevance of paleontology to climate change policy - Kießling, Wolfgang; Smith, Jansen; Raja, Nussaïbah Begum (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Paleontology has provided invaluable basic knowledge on the history of life on Earth. The discipline can also provide substantial knowledge to societal challenges such as climate change. The long-term perspective of climate change impacts on natural systems is both a unique selling point and a major obstacle to becoming more pertinent for policy-relevant bodies like the Intergovernmental Panel on Climate Change (IPCC). Repeated experiments on the impacts of climate change without anthropogenic disturbance facilitate the extraction of climate triggers in biodiversity changes. At the same time, the long timescales over which paleontological changes are usually assessed are beyond the scope of policymakers. Based on first-hand experience with the IPCC and a quantitative analysis of its cited literature, we argue that the differences in temporal scope are less of an issue than inappropriate framing and reporting of most paleontological publications. Accepting that some obstacles will remain, paleontology can quickly improve its relevance by targeting climate change impacts more directly and focusing on effect sizes and relevance for projections, particularly on higher-end climate change scenarios.
CRIS-Team Scopus Importer:2023-02-17
Keywords: biodiversity; climate change; IPCC; paleobiology

Increasing the equitability of data citation in paleontology: capacity building for the big data future - Smith, Jansen A.; Raja, Nussaïbah Begum; Clements, Thomas; Dimitrijevic, Danijela; Dowding, Elizabeth; Dunne, Emma; Gee, Bryan M.; Godoy, Pedro L.; Lombardi, Elizabeth M.; Mulvey, Laura; Nätscher, Paulina; Reddin, Carl J.; et al. (Paleobiology, 2023)
Data compilations expand the scope of research; however, data citation practice lags behind advances in data use. It remains uncommon for data users to credit data producers in professionally meaningful ways. In paleontology, databases like the Paleobiology Database (PBDB) enable assessment of patterns and processes spanning millions of years, up to global scale. The status quo for data citation creates an imbalance wherein publications drawing data from the PBDB receive significantly more citations (median: 4.3 ± 3.5 citations/year) than the publications producing the data (1.4 ± 1.3 citations/year). By accounting for data reuse where citations were neglected, the projected citation rate for data-provisioning publications approached parity (4.2 ± 2.2 citations/year) and the impact factor of paleontological journals (n = 55) increased by an average of 13.4% (maximum increase = 57.8%) in 2019. Without rebalancing the distribution of scientific credit, emerging “big data” research in paleontology—and science in general—is at risk of undercutting itself through a systematic devaluation of the work that is foundational to the discipline.<br
Keywords: Biodiversity; Open science; Paleobiology Database; Specimen-based; Taxonomy

Marine biological responses to abrupt climate change in deep time - Kießling, Wolfgang; Reddin, Carl James; Dowding, Elizabeth; Dimitrijevic, Danijela; Raja, Nussaïbah Begum; Kocsis, Ádám (Paleobiology, 2024)
Ancient changes in the biosphere, from organismic traits to wholesale ecosystem changes, can be aligned with climate forcing across the Phanerozoic. Clear examples of abrupt climate warming causing biodiversity crises are primarily found between the Permian and Paleogene periods. During these times, catastrophic events occurred, resembling the extreme climate scenarios projected for the near future. The paleobiologic literature around these events generally supports the hypothesis that abrupt climate change was a dominant trigger of extinction and/or ecological crisis. When climate change and climate history are considered, virtually all post-Paleozoic global biotic events can be confidently attributed to climatic change, with abrupt warming (hyperthermal events) leaving the most consistent fingerprint. The combined stress of deoxygenation and warming are sufficient to explain marine extinction patterns across most hyperthermal events. Although ocean acidification may have contributed, the direct role of pH on the extinction toll of organisms is not consistently demonstrated. Future research can enhance the correspondence between the magnitudes of climatic changes and their biological impacts, even though observed rates of change cannot currently be compared across different timescales. Mimicking multi-scale approaches in modern ecology, paleontological approaches to climate impact research will benefit from specifically targeting scaling relationships.

Mismatches of threat status and actual extinctions in Quaternary reef corals - Raja, Nussaïbah Begum; Lauchstedt, Andreas; Pandolfi, John M.; Kim, Sun W.; Budd, Ann F.; Kießling, Wolfgang (GSA 2020 Connects Online, 2020)
Species traits and spatial distributions influence the extinction risk of species as a result of abiotic and biotic change. We performed a comparative assessment of the relationship between traits and extinction risk of reef corals in the modern oceans against Plio-Pleistocene reef corals. We chose the Plio-Pleistocene as most of the corals during this time are still present today and their traits are thus comparable to those of modern corals. As such, the regional extinctions of reef corals during this time, attributed to climate change, may shed light on which traits contribute to the resilience or vulnerability of reef building corals in the face of contemporary ocean warming. We applied predictive modelling using two morphological and two distributional traits of 585 extant reef coral species together with data on extinction risk as reported by the International Union for Conservation of Nature (IUCN). This model was then validated against the fossil corals. Although our model performed well in the prediction of the extinction risk of modern corals (82% match), the match between our modelled extinction risk and observed extinction during the Plio-Pleistocene was not better than random. This suggests that either 1) the IUCN status for reef corals may not reflect true extinction risk, or 2) the drivers of extinction during the Plio-Pleistocene may be considerably different from the conditions currently observed in the oceans. This underlines the need to incorporate fossil data when assessing the vulnerability of extant species to climate chang

Modularity explains large-scale reef booms in Earth’s history - Raja, Nussaïbah Begum; Pandolfi, John M.; Kießling, Wolfgang (Facies, 2023)
Drivers of reef decline are well known both today and in the geological past. Considerably less is known about the preconditions for a pantropical expansion of coral reefs. The geological record of reef building is characterised by considerably long intervals with very limited reef expansion and geologically brief (< 20 million years) episodes of prolific, pantropical reef growth. Here, we propose a new "co-occurrence hypothesis" (COH), which posits that reefs thrive when fast-growing hypercalcifiers co-occur with encrusting organisms such as calcifying microbes or coralline algae to construct wave-resistant structures. While there is little evidence of the effect of abiotic drivers on reef proliferation, we find that positive co-occurrence patterns are significantly more common in reefal as compared to non-reefal communities, suggesting that biological interactions are more relevant in reefs than in non-reefs. Supporting COH, we also show that reefs after the end-Permian mass extinction became more modular in nature with limited membership in reef assemblages during reef booms than in typical periods of reef growth (background intervals). Modularity in reefs may have led to the stabilisation of reef ecosystems, giving them the ability to recover from small perturbations, promoting reefal carbonate accretion and prolific reef growth.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Co-occurrence; Modularity; Palaeobiology; Reefs

Morphological traits of reef corals predict extinction risk but not conservation status - Raja, Nussaïbah Begum; Lauchstedt, Andreas; Pandolfi, John M.; Kim, Sun W.; Budd, Ann F.; Kießling, Wolfgang (Global Ecology and Biogeography, 2021)
Aim The current assessment of extinction risk in reef corals by the International Union for Conservation of Nature (IUCN) has been criticized, because coral life-history traits associated with resilience are not reflected in the conservation status. We aimed to carry out a quantitative assessment of the link between reef coral traits and species extinction risk informed by extinctions of reef corals observed in the fossil record. Location Global. Time period Plio-Pleistocene and present day. Major taxa studied Scleractinian reef corals. Methods We used morphological traits, phylogenetic information and evidence of extinction during the Plio-Pleistocene to predict the extinction risk of contemporary reef corals. Our model was trained using 138 Caribbean fossil coral species and an automatic machine learning algorithm. We then used this model to predict the extinction risk of 674 modern coral species. Results Model validation confirmed 77% accuracy in predicting extinction risk of fossil corals. Extinction risk predicted by our model showed a near-random (57%) match with the IUCN conservation status. Our model also suggested that corals in the Least Concern or Near Threatened categories might be at higher risk of extinction than currently believed. Main conclusions Morphological traits of fossil corals linked to their extinction risk in the Plio-Pleistocene Caribbean Sea are known to reflect the vulnerability of extant corals. However, the results from our fossil-calibrated model do not match the IUCN assessment of reef corals, with increased overall extinction risk. This does not necessarily indicate near-future extinction risk, because fossil extinctions are spread over thousands of years. However, we show the applicability of using fossil data to inform the extinction risk of modern corals and recommend that future assessments of extinction risk of reef corals should consider incorporating the relationship between morphological traits and resilience, calibrated by fossil data, to maximize the utility of the extinction risk assessment. <br
Keywords: extinction risk; fossil record; predictive modelling; Red List; reef corals; traits

Origination and dispersal dynamics of Cenozoic marine plankton - Raja, Nussaïbah Begum; Kießling, Wolfgang (Annual Meeting of the Paleontological Society (Paläontologische Gesellschaft) 2019, 2019)

Out of the extratropics: the evolution of the latitudinal diversity gradient of Cenozoic marine plankton - Raja, Nussaïbah Begum; Kießling, Wolfgang (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2021)
Many ecological and evolutionary hypotheses have been proposed to explain the latitudinal diversity gradient, i.e. the increase in species richness from the poles to the tropics. Among the evolutionary hypotheses, the ‘out of the tropics’ (OTT) hypothesis has received considerable attention. The OTT posits that the tropics are both a cradle and source of biodiversity for extratropical regions. To test the generality of the OTT hypothesis, we explored the spatial biodiversity dynamics of unicellular marine plankton over the Cenozoic era (the last 66 Myr). We find large-scale climatic changes during the Cenozoic shaped the diversification and dispersal of marine plankton. Origination was generally more likely in the extratropics and net dispersal was towards the tropics rather than in the opposite direction, especially during the warmer climates of the early Cenozoic. Although migration proportions varied among major plankton groups and climate phases, we provide evidence that the extratropics were a source of tropical microplankton biodiversity over the last 66 Myr.<br
Keywords: macroevolution; biodiversity; marine plankton; climate change; biogeography

Regionalization of precipitation in Mauritius: a statistical approach - Raja, Nussaïbah Begum; Aydin, Olgu (Meteorological Applications, 2019)
The aim of this study was to quantify the regional precipitation patterns of Mauritius using the total mean annual precipitation of 52 meteorological stations for the period 1981–2010. Principal component analysis was first used to determine the significant variables influencing precipitation in Mauritius. A cluster analysis was then applied to group the stations according to the significant variables identified. Finally, a spatial interpolation of precipitation in Mauritius using the kriging with external drift technique was carried out to examine the spatial distribution of precipitation on the island. The principal component analysis results showed that elevation and coastal proximity caused the most variance in the dataset with respect to precipitation. Using the cluster analysis and kriging results, six regions of precipitation were determined: three inland and three coastal regions. A decreasing gradient in precipitation between the southeast and northwest is observed due to the southeast trade winds and the altitudinal difference between the coastal areas and the central plateau. The central plateau represents a distinct precipitation zone which receives the highest precipitation on the island. The windward-facing south and eastern highlands experience orographic precipitation as a result of adiabatic air expansion and therefore are more humid. On the other hand, the northeast highlands region, together with the north and western coasts which lie in the leeward rain shadow, are notably drier.
CRIS-Team Scopus Importer:2019-07-02
Keywords: cluster analysis (CA); kriging; Mauritius; precipitation; principal component analysis (PCA); regional precipitation pattern

Revisiting the long-term biodiversity dynamics of reef builders in a novel Bayesian framework - Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (13th International Symposium on Fossil Cnidaria, 2019)

Scientific collaborations between Latin America and Europe: An approach from science diplomacy towards international engagement - Echeverría-King, Luisa F.; Fossati, Aura; Raja, Nussaïbah Begum; Bonilla, Kleinsy; Urbani, Bernardo; Whiffen, Radenka Krsmanović; Vizinová, Tereza (Science and Public Policy, 2023)
International collaborations show asymmetries and imbalances that influence how countries take part in international relations. In this context, science diplomacy (SD) could offer possibilities towards building partnerships and meaningful engagement between Europe and Latin America. The purpose of this article is to analyse how scientific collaborations between Latin American and European researchers are carried out, observing trends, behaviours, and perceptions. Qualitative methodologies and the analysis of empirical data collected through a survey allow the extraction of relevant experiences from real cases of international joint projects. Findings indicate that addressing the asymmetries in the collaboration between partnering researchers from Europe and Latin America is essential, and SD approaches may facilitate such endeavour. SD may not represent a panacea; however, it seems to facilitate the internationalisation of research in terms of mobility, international scientific collaborations, and knowledge exchange with under-represented actors in traditional international scientific schemes, such as indigenous communities.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Europe-Latin America; Global South; science diplomacy; scientific collaborations; transnational research

Scientometric trends in Burmese amber research - Dunne, Emma; Raja, Nussaïbah Begum (Paleontological Association Annual Meeting, 2020)
Discoveries of fossil inclusions in Burmese (Myanmar) amber have attracted considerable attention due to their exquisite preservation, which offers an unparalleled window into Cretaceous forest ecosystems. However, research on Burmese amber has also attracted controversy due to its alleged role in funding internal conflict, resulting in a devastating humanitarian crisis. The palaeontological community is not yet unified on how to ethically adjust research practices in response to this situation. Using bibliometric methods and networks analyses, we investigated the scientometric trends in research publications on fossils in Burmese amber, and quantitatively examined the collaborative networks of their authors. We find that in the last 30 years, research activity on Burmese amber has generally increased, with a noticeable escalation within the last five years, coincident with the military takeover of the amber mines. The majority of publications are authored by researchers based in countries of the Global North and lack Burmese co-authors, indicating weak or absent collaborations with local researchers and communities. This practice of ‘parachute science’ is harmful generally, but in a conflict region it is acutely problematic because it erodes confidence about whether fossil specimens are – or even can be – ethically collected and trade

Spatial-temporal analysis of precipitation characteristics in Artvin, Turkey - Aydin, Olgu; Raja, Nussaïbah Begum (Theoretical and Applied Climatology, 2020)
The region of Artvin, located in the northeast of Turkey, usually experiences high-intensity precipitation events that occur within a short-time period. Along with other environmental impacts, these events also lead to flash floods in this region. The purpose of this study was to evaluate the changing spatial and temporal characteristics of precipitation on August 24, 2015 and November 11 to 12, 2015 that triggered flash floods and landslides in Artvin. We apply spatiotemporal (ST) kriging as a tool to investigate these ST patterns. The average hourly precipitation data were used, taking episodes of heavy rainfall into account. Our results show that precipitation reached the highest values of 30–50 mm between 8:00 and 9:00 pm in the Hopa district on August 24, 2015. On November 11, 2015, rainfall values reached ≥ 15 mm at 4:00 PM in the Borçka district. During both events occurred on November 12, 2015, it rained for 7 h continuously with precipitation values ranging between 5 and 10 mm. The duration of the precipitation lasted for 8 h. In addition, flood events also occurred in the districts of Arhavi and Murgul. This highlights that these districts are vulnerable in the Artvin region and paves the way for decision-makers to implement measures against flash floods in these at-risk districts. In conclusion, the analysis of spatiotemporal characteristics of heavy rainfall events represents an indispensable basis to ensure that necessary precautions regarding flash flood events in the city are take
Keywords: precipitation characteristics; flood events; space and time; kriging; artvin

The moral and legal imperative to return illegally exported fossils - Cisneros, Juan; Ghilardi, Aline Marcele; Raja Schoob, Nussaibah Begum; Stewens, Paul (Nature Ecology & Evolution, 2021)

The overlooked realities of sampling bias - Raja, Nussaïbah Begum; Dunne, Emma; Khan, Tasnuva; Nätscher, Paulina (GSA Annual Meeting 2020, 2020)
Analyses of past global biodiversity are severely hindered by sampling biases and gaps in the fossil record. These have previously been attributed to several geological and biological factors such as rock outcrop area, taxonomic definitions, fossil abundance, among others. In many cases, inferred so-called global diversity curves only reflect regional diversity of well-sampled localities. However, global compilations of fossil occurrences, such as from the Paleobiology Database (PBDB), not only reflect the physical aspects of the fossil record, but also document the historical compilation of this data over more than two centuries. In this study, we find that socioeconomic factors such as wealth, language and security may help to explain spatial variation in the compiled data of the PBDB. Countries with high per capita gross domestic product (GDP; implying greater access to research funds), a population with high English proficiency, and greater political stability were generally found to be the countries from which higher number of collections originated and documented in the PBDB. Similarly, we found that these countries also contributed to a majority of the compiled literature from which the data was extracted. The factors identified in this study influence fossil data collection, access and availability by determining who has access to specimens and the ability to do research. As such, efforts towards achieving an understanding of the “real” past global diversity will benefit from investing in scientific education, and more research and collaborations in countries at a disadvantage, with a focus on improving local geological and paleontological knowledg

The Return of Fossils Removed Under Colonial Rule - Dunne, Emma; Raja Schoob, Nussaibah Begum; Stewens, Paul (2022)
Debates on the restitution of colonial loot usually focus on art, antiquities, religious artefacts, and similar objects. Many fossils of considerable scientific and cultural value were also removed under colonial rule, yet they rarely feature in these discussions despite being classified as cultural objects. This article seeks to shed light on the colonial removal of fossils and explore potential avenues for their return under public international law. Instead of focusing on the (il-)legality of colonial takings, we argue that the right to access culture has developed from the right to participate in cultural life in Article 15(1)(a) of the International Covenant on Economic, Social and Cultural Rights (ICESCR), which provides, if not a solid legal basis, a valuable set of arguments for former colonies requesting the return of fossils looted from their countries/territories of origin. The case study of the negotiations on the return of the Broken Hill skull before the UNESCO Intergovernmental Committee for Promoting the Return of Cultural Property to its Countries of Origin or its Restitution in Case of Illicit Appropriation (ICPRCP) highlights the potential of this mechanism of dispute resolution with respect to fossils. <br

Trend analysis of annual precipitation of Mauritius for the period 1981–2010 - Raja, Nussaïbah Begum; Aydin, Olgu (Meteorology and Atmospheric Physics, 2019)
This study researched the precipitation variability across 53 meteorological stations in Mauritius and different subregions of the island, over a 30-year study period (1981–2010). Time series was investigated for each 5-year interval and also for the whole study period. Non-parametric Mann–Kendall and Spearman’s rho statistical tests were used to detect trends in annual precipitation. A mix of positive (increasing) and negative (decreasing) trends was highlighted for the 5-year interval analysis. The statistical tests nevertheless agreed on the overall trend for Mauritius and the subregions. Most regions showed a decrease in precipitation during the period 1996–2000. This is attributed to the 1998–2000 drought period which was brought about by a moderate La Niña event. In general, an increase in precipitation levels was observed across the country during the study period. This increase is the result of an increase in extreme precipitation events in the region. On the other hand, two subregions, both located in the highlands, experienced a decline in precipitation levels. Since most of the reservoirs in Mauritius are located in these two subregions, this implies serious consequences for water availability in the country if existing storage capacities are kept.
CRIS-Team Scopus Importer:2019-07-19

What is conservation paleobiology? Tracking 20 years of research and development - Dillon, Erin M; Pier, Jaleigh Q; Smith, Jansen A.; Raja Schoob, Nussaibah Begum; Dimitrijevic, Danijela; Austin, Elizabeth L; Cybulski, Jonathan D.; De Entrambasaguas, Julia; Durham, Stephen R; Grether, Carolin; Haldar, Himadri Sekhar; Kocáková, Kristína; et al. (Frontiers in Ecology and Evolution, 2022)
Conservation paleobiology has coalesced over the last two decades since its formal coining, united by the goal of applying geohistorical records to inform the conservation, management, and restoration of biodiversity and ecosystem services. Yet, the field is still attempting to form an identity distinct from its academic roots. Here, we ask a deceptively simple question: What is conservation paleobiology? To track its development as a field, we synthesize complementary perspectives from a survey of the scientific community that is familiar with conservation paleobiology and a systematic literature review of publications that use the term. We present an overview of conservation paleobiology’s research scope and compare survey participants’ perceptions of what it is and what it should be as a field. We find that conservation paleobiologists use a variety of geohistorical data in their work, although research is typified by near-time records of marine molluscs and terrestrial mammals collected over local to regional spatial scales. Our results also confirm the field’s broad disciplinary basis: survey participants indicated that conservation paleobiology can incorporate information from a wide range of disciplines spanning conservation biology, ecology, historical ecology, paleontology, and archaeology. Finally, we show that conservation paleobiologists have yet to reach a consensus on how applied the field should be in practice. The survey revealed that many participants thought the field should be more applied but that most do not currently engage with conservation practice. Reflecting on how conservation paleobiology has developed over the last two decades, we discuss opportunities to promote community cohesion, strengthen collaborations within conservation science, and align training priorities with the field’s identity as it continues to crystallize.<br